ASSOCIATION BETWEEN GUSTATORY AND OLFACTORY DYSFUNCTIONS AND GHRELIN, IL-6, AND IL-10 LEVELS IN COVID-19 PATIENTS - Gönül Şeyda Seydel; İnayet Güntürk; Cevat Yazıcı; Füsun Ferda Erdoğan (Sabiad)
Objective: The aim of this study was to examine the association between gustatory and olfactory dysfunctions and ghrelin, IL-6, and IL-10 levels in patients with COVID-19. Materials and Methods: A total of 80 COVID-19 patients were enrolled in the study: 57 patients with gustatory and/or olfactory dysfunctions and 23 patients without gustatory or olfactory dysfunctions. The plasma ghrelin, IL-6, and IL-10 levels of all patients were determined using the ELISA method. Results: COVID-19 patients with gustatory and/or olfactory dysfunctions had higher IL-6 and lower ghrelin and IL-10 levels compared with COVID19 patients without gustatory or olfactory dysfunctions (p<0.001). Conclusions: These results demonstrate that an inflammatory process mediated by ghrelin, IL-6, and IL-10 contributes to the development of gustatory and olfactory dysfunctions in COVID-19 patients.